Ocular Tolerability and Immune Response to Corneal Intrastromal AAV-IDUA Gene Therapy in New Zealand White Rabbits - Liujiang Song; Jacquelyn J. Bower; Telmo Llanga; Jacklyn H. Salmon; Matthew L. Hirsch; Brian C. Gilger (Molecular Therapy: Methods & Clinical Development, 2020)
The chronic ocular toxicity, tolerability, and inflammation following corneal intrastromal injection of saline or escalating doses of an adeno-associated virus (AAV) containing a codon-optimized α-l-iduronidase (AAV-opt-IDUA) expression cassette were evaluated in New Zealand White rabbits. Corneal opacity following corneal intrastromal injection resolved by 24 h. Mild elevation of clinical ocular inflammation was observed 24 h after injection, but it returned to baseline by day 7 and no abnormalities were noted through 6 months of observation after injection. Vector genomes and IDUA cDNA were detected in the injected corneas in a dose-dependent manner. Both the lowest administered AAV-opt-IDUA dose, shown to be effective in mucopolysaccharidosis type I (MPS I) dogs, and a 10-fold higher dose of AAV-opt-IDUA resulted in no detectable immunologic response or adverse effect in rabbits. Vector genomes outside of the eye were rarely detected following corneal intrastromal injection of AAV-opt-IDUA, and neutralizing antibodies to the AAV capsid were not present at the experimental conclusion. This study, combined with our previous studies in MPS I dogs, suggests that AAV-opt-IDUA corneal gene therapy following corneal intrastromal injection of AAV-opt-IDUA has the potential to prevent and reverse blindness in MPS I patients in a safe and effective manner.